2016
DOI: 10.1186/s12891-016-1073-0
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative pain catastrophizing and postoperative pain after total knee arthroplasty: a prospective cohort study with one year follow-up

Abstract: BackgroundPain relief is likely to be the most important long-term outcome for patients undergoing total knee arthroplasty (TKA). However, research indicates that persistent pain (> 3 months) is a considerable problem, affecting up to 34 % of patients. Pain catastrophizing might contribute to acute and persistent pain experienced after surgery. The primary aim of the present study was to examine the association between preoperative pain catastrophizing and postoperative pain in patients undergoing TKA up to on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
2
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 59 publications
(74 reference statements)
4
43
2
3
Order By: Relevance
“…Our sample exhibited low levels of pain-catastrophizing at baseline (Mean PCS=15.01) similarly to those reported in other studies of KOA patients [17; 18], but lower than baseline PCS scores reported in intervention studies in other chronic pain conditions [5; 22; 28]. This could have caused a floor effect, and possibly larger effects might be observed in patients with greater pain-catastrophizing.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Our sample exhibited low levels of pain-catastrophizing at baseline (Mean PCS=15.01) similarly to those reported in other studies of KOA patients [17; 18], but lower than baseline PCS scores reported in intervention studies in other chronic pain conditions [5; 22; 28]. This could have caused a floor effect, and possibly larger effects might be observed in patients with greater pain-catastrophizing.…”
Section: Discussionsupporting
confidence: 81%
“…One such target is pain-catastrophizing, a cognitive and emotional coping style which is considered one of the most salient psychological factors contributing to heightened acute and chronic pain [36; 46]. In KOA, catastrophizing is associated with pain and disability [44] and is a risk factor for continuation of chronic pain following total knee arthroplasty [3; 18; 54]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have suggested that female patients have higher levels of catastrophizing than male patients, 2 but others have not corroborated this. 14,15 This may be a function of variation in sample composition. Jacobsen and colleagues 16 proposed that younger patients manifest higher levels of pain catastrophizing than older patients and suggested that this may be due to less experience coping with painful events.…”
Section: Discussionmentioning
confidence: 99%
“…Total knee arthroplasty, a common orthopedic reconstructive procedure, has helped many to overcome the disability and pain from osteoarthritis of the knee [1]. Despite the gratifying results, a major complication of hemorrhage is inevitable to prevent but can be controlled [2].…”
Section: Introductionmentioning
confidence: 99%